Performative Inclusion and Diplomatic Emotion: Strategic Crisis Communication of Global Food Security Leaders on Social Media - Hasbullah, Nor Azila; Nair, Ramesh; Ismail, Isma Noornisa (Masyarakat Linguistik Indonesia Universitas Andalas, 2026)
Existing crisis communication frameworks are mostly orientated toward sheltering the reputation of an organization, thus limited insights are presented into how global leaders sustain legitimacy and solidarity during prolonged humanitarian crises, such as global food security issues. Addressing this gap, this study examines how six leaders from major international food security institutions (UN, FAO, WFP, IFAD, IFPRI, and USAID) employed rhetorical strategies on X (formerly Twitter) to address food security challenges during the COVID-19 pandemic (2020–2022). The study investigates five communication styles: inclusive language, thematic framing, emotive discourse, rhetorical markers, and temporal storytelling by using qualitative content analysis of 302 tweets and following the Restorative Rhetoric framework. Findings show that leaders used strategic, inclusive, and empathetic language, narrative coherence, and solution-oriented framing to gain support and visualize institutional legitimacy. This study proposes two novel concepts: performative inclusion, which refers to the strategic use of rhetoric by leaders to convey unity while concealing persistent power asymmetries, and diplomatic emotion, the bounded expression of empathy regulated by institutional authority. These insights extend strategic communication theory by showing how leaders balance authenticity, authority, and legitimacy in digital crisis contexts. The study offers guidance for institutions on designing communication strategies with a combination of empathy, participation, and credibility in managing global crises.